Nonsurgical management of two unusual cases of dens in dente - Gupta R; Tewari S (Wolters Kluwer Medknow Publications, 2005)
The management of two unusual cases of dens invaginatus in a maxillary and a mandibular lateral incisor with a periradicular lesion are reported. The patient presented with pain and localized swelling. Despite the complex anatomy and diagnosis of dens invaginatus, nonsurgical root canal treatment was performed successfully. Furthermore essential clinical considerations and treatment options are suggested. Early diagnosis and management are important to avoid complications.